If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = 12x + -15y Solving -15 = 12x + -15y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -15 + -12x = 12x + -12x + -15y Combine like terms: 12x + -12x = 0 -15 + -12x = 0 + -15y -15 + -12x = -15y Add '15' to each side of the equation. -15 + 15 + -12x = 15 + -15y Combine like terms: -15 + 15 = 0 0 + -12x = 15 + -15y -12x = 15 + -15y Divide each side by '-12'. x = -1.25 + 1.25y Simplifying x = -1.25 + 1.25y
| 4(7n-8)=-256 | | -4(c-19)=8 | | 5x+18=3(2+3x) | | (y*0.06)+y=10 | | 6f-8=2 | | 4/3t=-9 | | -10=1-u | | 12(e/8)=30 | | 3m+10=8m-55 | | -3(-4x+2)=-102 | | z-10/-3=0 | | 9y=72x | | n^2-8=3n | | 5U=36+u | | 20+5x=20+4x | | -5b-4b-5=0 | | 4/c=2 | | 2x=-x+-2 | | X^3+5x+4x=0 | | N^2+4m-21=0 | | 2p^2=-6+7p | | 12m+-5m+m=6(m+1) | | 8a^2+4=36 | | 5x-20=2+5 | | 8(6-7m)=328 | | 5n^2=14n+3 | | 7x^2=26x+8 | | 4log=x | | 3y^2=21-30y | | -3y-9=5y+7 | | 8y^4-6y^3= | | 3x+10=8x-55 |